A Two-stage Malware Detection Architecture Inspired by Human Immune System - Salah, MAF; Marhusin, MF; Sulaiman, R (IEEE, 2024)
Malware sophistication is on the rise and continue being a serious threat against privacy, availability and integrity of information. This paper proposed an architecture which consist of two detectors. The first detector observes for malware in general. It will classify an executable if whether it is benign or malign and updates its Knowledge Base dynamically. The second detector is a specialised one, aiming to detect ransomware via its deep scan capability. This detector will be activated if the first detector senses the presence of ransomware pre-execution activities. The detector will decide whether a program is a ransomware or not and dynamically update its Knowledge Base dynamically.